2019
DOI: 10.1155/2019/2580207
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Modulates LPA Function to Inhibit the Proliferation and Inflammation of FLS-RA via p38/ERK MAPK Pathway Mediated by LPA1

Abstract: Objective This study aimed to investigate whether berberine exerted anti-inflammatory and antiproliferative effects on the fibroblast-like synoviocytes of rheumatoid arthritis (FLS-RA) through regulating the lysophosphatidic acid (LPA) function. Methods Firstly, the expression levels of LPA and lysophosphatidic acid receptor 1 (LPA1) in RA patients, osteoarthritis (OA) patients, and healthy controls were detected. Moreover, molecular docking was employed to characterize the binding sites of berberine in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
(41 reference statements)
1
25
0
Order By: Relevance
“…Moreover, the identification of roles independent of infections led to the extension of what has been called "sterile inflammation" (e.g., injury, illness, or aging). In particular, the activity of p38α has been associated with (a) the progression of the expression of protein markers of the aging phenotype [20][21][22]; (b) the development of inflammation and oxidative stress [10,23] associated with neurodegeneration, including Alzheimer's [24][25][26], lipopolysaccharide (LPS) [27,28], and Parkinson's [29,30] diseases; cardiovascular [31] and musculoskeletal diseases; diabetes [32]; rheumatoid arthritis [33]; and toxin-induced preterm birth [34]. Importantly, small molecule inhibitors of the p38 MAPK family have been developed, and show efficacy in blocking the production of proinflammatory cytokines, such as interleukin (IL)-1β and tumor necrosis factor alpha (TNF-α) [35].…”
Section: P38 Mitogen-activated Protein Kinases (P38-mapk)mentioning
confidence: 99%
“…Moreover, the identification of roles independent of infections led to the extension of what has been called "sterile inflammation" (e.g., injury, illness, or aging). In particular, the activity of p38α has been associated with (a) the progression of the expression of protein markers of the aging phenotype [20][21][22]; (b) the development of inflammation and oxidative stress [10,23] associated with neurodegeneration, including Alzheimer's [24][25][26], lipopolysaccharide (LPS) [27,28], and Parkinson's [29,30] diseases; cardiovascular [31] and musculoskeletal diseases; diabetes [32]; rheumatoid arthritis [33]; and toxin-induced preterm birth [34]. Importantly, small molecule inhibitors of the p38 MAPK family have been developed, and show efficacy in blocking the production of proinflammatory cytokines, such as interleukin (IL)-1β and tumor necrosis factor alpha (TNF-α) [35].…”
Section: P38 Mitogen-activated Protein Kinases (P38-mapk)mentioning
confidence: 99%
“…71 The levels of plasma and synovial LPA in RA patients are found to be significantly higher than those in healthy subjects. 77 LPA is suggested to be an independent risk factor of synovial hyperplasia in RA in addition to the high burden of inflammation. 77 During inflammation, LPA is majorly generated in activated platelets through the degradation of lysophosphatidylcholine by secretory lysophospholipase D termed as autotaxin (ATX) that is detected to be highly elevated in the activated arthritic synovial fluid from RA patients and AIA rats, 77,78 and berberine has been indicated to decrease the expression of ATX in RAFLS cells and thus decrease LPA levels in RA condition.…”
Section: Lpa/mapk Signalling Pathwaymentioning
confidence: 99%
“…In the previous report [27,28], downstream of LPA receptor activation, MAPK/ERK signaling pathway can be activated by LPA. In our study, we found that LPA treatment on swine macrophages strongly induced biological pathway for "role of MAPK signaling in the pathogenesis of influenza" and its related genes to be differentially regulated (Figure 3).…”
Section: Discussionmentioning
confidence: 82%
“…We also identified KA-1002 treatment downregulated LPA-induced gene enrichment set of "role of MAPK signaling in the pathogenesis of influenza" (Figure 3). MAPK signaling is well-known for its role in inflammation [28]. However, the gene enrichment set of "IL-10 signaling" was increased by KA-1002 treatment compared to LPA mediated inflamed swine macrophages (Figure 3).…”
Section: Discussionmentioning
confidence: 96%